Transcriptomic analysis reveals distinct mechanisms of carvone and lipopeptide crude extract from Bacillus velezensis JZ in the postharvest biocontrol of Alternaria alternata on strawberries - Lizhu Shao; Boyuan Zhang; Xueling Zhao; Yating Wang; Ziyu Wang; Miaomiao Yang; Zunzun Qi; Yuansen Hu; Na Liu; Peng Li; Li Zhang (Postharvest Biology and Technology, 2027)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

A reference-guided large language model workflow for mobile phase selection in thin-layer chromatography enabled by a polarity-space tetrahedron strategy - Wei-Song Kong; Song-Xue Shao; Li-Na Zhu; Xi Yu (Analytica Chimica Acta, 2026)

Fermentation modulates wheat germ gliadin-based nanodelivery systems loaded with wheat bran polyphenols: Physicochemical properties, interaction mechanism, and functional performances - Ai-Mei Liao; Shao-Kang Yang; Meng-Yu Gao; Siyi Han; Long Pan; Jayani Chandrapala; Haiyan Gao; Dandan Zhai; Jun-Wei Chen; Na Liu; Peng Li (Food Bioscience, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

An integrated multi-omics approach for deciphering podophyllotoxin-induced nephrotoxicity via the microbiome-gut-kidney (MGK) axis based on the toxicological evidence (TEC) concept - Xiaole Guo; Yu Wang; Lei Wang; Yan Lei; Ri-na Sa; Lili Li; Shengnan Xia; Xiaoming Lin; Chuanxin Liu; Yuanyang Shao (Journal of Molecular Histology, 2026)

Insights into the ascorbate-glutathione cycle and methylglyoxal detoxification systems during leaf yellowing of macadamia - Weihai Yang; Yuanbao Cai; Dongliang Hou; Qianqian Ouyang; Jun Chen; Wenjun Lei; Lizhen Zeng; Xiaopeng Li; Qiusheng Xiao; Na Chen; Qin Shao (Protoplasma, 2026)

Mechanistic insights into efficient H2O2 production by a carbon nitride homojunction under different conditions - Guangyuan Li; Binrong Li; Na Li; Wei Gao; Yongqi Shao; Xin Li; Wenli Li; Wei Nie; Feiteng Sun; Jingyuan Huang; Qi Gong; Xuedong Wang (Chemical Engineering Journal, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Self-driven dynamic homogeneous to heterogeneous switching on pyrite/hematite mineral for sustainable fenton-like water cleanup - Binrong Li; Yongqi Shao; Wei Gao; Guangyuan Li; Chen Wang; Na Li; Xing Xu; Xuedong Wang (Journal of Hazardous Materials, 2026)

Effects of nutrient forms on the bloom dynamics and phytoplankton community associated with Prorocentrum cordatum - Chuang Li; Yicheng Wang; Na Jiang; Shuangqing Li; Chenyang Shao; Fengyuan Zhang; Huajun Zhang; Weizhong Chen; Hailong Huang; Haibo Jiang (Harmful Algae, 2026)

Forecasting China’s carbon prices using a TVFEMD-DLinear framework incorporating climate policy uncertainty - Haozhen Li; Feng Gao; Na Zuo; Xin Gao; Tianming Shao; Xunzhang Pan (Environmental Impact Assessment Review, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

The multi-carboxyl metal-organic framework MIL-101(Fe) effectively adsorbs total purines from whole soybean seeds - Deshuai Shao; Cui He; Na Li; Yuqing Gao; Xiaoyu Hu; Yingrun Cai; Qinqin Zhang; Jiahui Yao; Shuo Wang; Yifan Yang; Jiayi Pan; Huihui Gao; et al. (Food Chemistry, 2026)

Genome analysis and secondary metabolite characterization of Bacillus velezensis JZ as a potential biocontrol agent - Li Zhang; Lizhu Shao; Boyuan Zhang; Yuting Li; Ziyu Wang; Shuhong Song; Miaomiao Yang; Boshen Wang; Dandan Zhai; Na Liu; Peng Li (Physiological and Molecular Plant Pathology, 2026)

Scalable wet-spun stretchable conductive fibers with SWCNT-enhanced mechanical and electrical properties for multifunctional wearables - Xu Zhao; Zirong Luo; Tuanzhang Li; Wenfa Mao; Fangting Mo; Yanqiu Shao; Shuang Li; Jizhen Zhang; Na Kong; Jihua Li; Jinlong Tao (Chemical Engineering Journal, 2026)

Free radical switching behavior between initial neutral and buffer neutral condition during Fenton-like degradation over pyrite/hematite mineral - Wei Gao; Binrong Li; Yongqi Shao; Guangyuan Li; Chen Wang; Na Li; Xuedong Wang (Environmental Research, 2025)

Ir single-atom sites stabilized by Ir-O-Ce4-δ coordination for high-efficiency PEMWE - Jianying Wang; Xu Luo; Tongzhou Li; Jingchen Na; Wanxiu Pang; Hongjie Zhang; Jinkai Hao; Zhigang Shao (Chemical Engineering Journal, 2025)

Lignin nanoparticles mediated self-adhesive and conductive hydrogel electrolytes for high-performance flexible supercapacitors - Jiabin Han; Yuxin Song; Jiangbo Li; Bing Wang; Jian Zhang; Shuyi Li; Xingwen Wang; Na Li; Xueru Sheng; Haiqiang Shi; Changyou Shao; Runcang Sun (Chemical Engineering Journal, 2025)

Nature-inspired water purification: Integrating riverbank filtration and biofilm-regulating nanofiltration - Na Li; Yongwang Liu; Hongting Wan; Li Long; Juntao Xing; Senlin Shao; Gang Liu; Walter G.J. van der Meer (Water Research, 2025)

Breaking genetic linkage barriers to improve brown planthopper resistance and grain yield in japonica rice - Wenhui Wang; Jun He; Yunlong Wang; Na Li; Quanguang Sun; Menglong Zhang; Qi Li; Haosen Xu; Kun Shao; Shihao Zhang; Shijia Liu; Liangming Chen; et al. (Theoretical and Applied Genetics, 2025)

Effects of dietary protein-oxidized soybean meal and quercetin on gel properties, microstructure, molecular structure and proteomics of egg white in laying hens - Hengzhi Li; Na Chen; Yun Shao; Chunxiao Wang; Yanmin Zhou; Shugang Li; Shuangjie Zhu (Food Chemistry, 2025)

GmEXPA11 facilitates nodule enlargement and nitrogen fixation via interaction with GmNOD20 under regulation of GmPTF1 in soybean - Xinzhu Xing; Hui Du; Zhanwu Yang; Hua Zhang; Na Li; Zhenqi Shao; Wenlong Li; Youbin Kong; Xihuan Li; Caiying Zhang (Plant Science, 2025)

Discovery of isopentenyl flavonoids with inhibitory activity against hepatocellular carcinoma cells based on DeepSAT - Qing Wang; Ben‐Song Xin; Wen-Long Kou; Li-Na Gao; Gu-Xue Zhang; Yan-Jiao Qiao; Guo‐Dong Yao; Xiao‐Xiao Huang; Shao‐Jiang Song (Phytochemistry, 2025)

Spatial and temporal distribution, fate, and potential health risks of microplastics in urban indoor air - Liyuan Peng; Na Zheng; Qirui An; Xiaoqian Li; Siyu Sun; Yunyang Li; Jingze Yu; Fan Shao; Yingxi Qiu; Shuyue Zhang (Gondwana Research, 2025)

Is the pollutant removed by the rejection of nanofiltration (NF) membranes in a NF-based membrane bioreactor (MBRNF)? - Chu Zhou; Xuan Zhou; Fujie Kuang; Na Li; Senlin Shao (Desalination, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Experimental study on oil removal performance and anodic dissolution characteristics during the treatment of marine oil spills using electrocoagulation - Boyan Shao; Yang Liu; Wenming Jiang; Na Chen; Jiaqi Wang; Juanjuan Li (Journal of Water Process Engineering, 2024)

Morphology and elemental composition of individual solid dust particles: From different sources to the atmosphere - Wenhua Wang; Mengyang Wang; Longyi Shao; Xiuyan Zhou; Zhe Zhao; Na Li; Hui Zhou; Weijun Li (Atmospheric Environment, 2024)

Nitrogen addition alleviates the negative effects of reduction in precipitation on soil multifunctionality in a typical steppe - Yan Shen; Yonghong Luo; Lan Du; Ru Tian; Wenqian Shao; Jiatao Zhang; Na Li; Jinbao Zhang; Shan Wang; Mohsin Mahmood; Zhuwen Xu (Applied Soil Ecology, 2024)

Pharmacoproteomics reveals energy metabolism pathways as therapeutic targets of ivermectin in ovarian cancer toward 3P medical approaches - Zhijun Li; Na Li; Marie Louise Ndzie Noah; Qianwen Shao; Xianquan Zhan (EPMA Journal, 2024)

The effects of roots and earthworms on aggregate size distribution and their associated carbon under contrasting soil types and soil moisture conditions - Na Mao; Xiangdong Li; Xiaorong Wei; Mingan Shao (CATENA, 2024)

Drought and nitrogen deposition regulate plant nutrient resorption in a typical steppe - Yonghong Luo; Yan Shen; Ahmed Salah Elrys; Lan Du; Mohsin Mahmood; Jiatao Zhang; Haiyan Ren; Jinbao Zhang; Na Li; Ru Tian; Wenqian Shao; Ahmed S.M. Elnahal; et al. (Agriculture, Ecosystems & Environment, 2024)

In vitro generation of trophoblast like stem cells from goat pluripotent stem cells - Qin Na; Siyu Zhang; Peng Shao; Yu Jia; Yanqiu Wang; Mengyi Wei; Yanglin Chen; Chen Chen; Lixia Zhao; Zixin Wang; Yongli Song; Baojiang Wu; et al. (Theriogenology, 2024)

Bio-inspired gradient poly(lactic acid) nanofibers for active capturing of PM0.3 and real-time respiratory monitoring - Guiying Zhu; Cunmin Wang; Ting Yang; Na Gao; Yifan Zhang; Jintuo Zhu; Xinjian He; Jiang Shao; Shihang Li; Mingming Zhang; Shenghui Zhang; Jiefeng Gao; et al. (Journal of Hazardous Materials, 2024)

Novel design of simplified β-hairpin antimicrobial peptide as a potential food preservative based on Trp-pocket backbone - Changxuan Shao; Yuanmengxue Wang; Guoyu Li; Hongrui Guan; Yongjie Zhu; Licong Zhang; Na Dong; Anshan Shan (Food Chemistry, 2024)

Clinically relevant immune subtypes based on alternative splicing landscape of immune-related genes for lung cancer advanced PPPM approach - Na Li; Wenshuang Jia; Jiahong Wang; Qianwen Shao; Xiaoxia Feng; Zhijun Li; Wenhao Sun; Ming Kang; Dongming Hu; Ligang Xing; Xianquan Zhan (EPMA Journal, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Summer heatwaves promote harmful algal blooms in the Fuchunjiang Reservoir, an important drinking water source - Shiwen He; Yunlin Zhang; Na Li; Kun Shi; Yibo Zhang; Boqiang Qin; Guangwei Zhu; Mingliang Liu; Keqiang Shao (Journal of Environmental Management, 2024)

MicroRNA-322-5p targeting Smurf2 regulates the TGF-β/Smad pathway to protect cardiac function and inhibit myocardial infarction - Liping Guo; Ke Li; Yan Ma; Huaiming Niu; Jun Li; Xin Shao; Na Li; Yuehui Sun; Haixiong Wang (Human Cell, 2024)

Achieving zero fouling in the ultrafiltration for secondary water supply systems in the absence of residual chlorine - Huizhi Hu; Fang Xu; Rui Wang; Chu Zhou; Na Li; Senlin Shao (Water Research, 2024)

Polar peripheral substituent-regulated organic/inorganic hybrid photocatalysts promoting the degradation of phenolic pollutants - Sheng-Hua Ma; Wei-Liang Jin; Hong-Xia Zhang; Shao-Cong Li; De-Ming Kong; Li-Na Zhu (Journal of Environmental Chemical Engineering, 2024)

Appropriateness of introducing earthworms into sustainable agriculture from the perspective of soil carbon emissions - Xiangdong Li; Na Mao; Weixin Zhang; Xiaorong Wei; Tong Liu; Jiong Cheng; Ming’an Shao (Soil and Tillage Research, 2024)

Removing refractory organic substances from landfill leachate using a nanofiltration membrane bioreactor: Performance and mechanisms - Chu Zhou; Na Li; Wenbin Guo; Rui Wang; Yaohua Yan; Senlin Shao (Chemical Engineering Journal, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

Covalently linked MOF@COF direct Z-scheme heterojunction for visible light-driven photocatalytic degradation of flotation agents - Hong-Xia Zhang; Sheng-Hua Ma; Hai-Xian Wang; Shao-Cong Li; Hai-Yun Shen; De-Ming Kong; Feng-Ying Wang; Li-Na Zhu (Journal of Environmental Chemical Engineering, 2024)

Microbiota-accessible carbohydrates enhance the biological properties and promote colonization of Lactiplantibacillus plantarum ZDY2013 in the intestinal tract of weaned rats - Jinmei Li; Kaisheng Shao; Na Zhang; Jinlin Lu; Zhihong Zhang; Hua Wei (Food Bioscience, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Revolutionizing material design for protonic ceramic fuel cells: Bridging the limitations of conventional experimental screening and machine learning methods - Idris Temitope Bello; Daqin Guan; Na Yu; Zheng Li; Yufei Song; Xi Chen; Siyuan Zhao; Qijiao He; Zongping Shao; Meng Ni (Chemical Engineering Journal, 2023)

Quantitative phosphoproteomics reveals molecular pathway network alterations in human early-stage primary hepatic carcinomas: potential for 3P medical approach - Yuping Zhang; Na Li; Lamei Yang; Wenshuang Jia; Zhijun Li; Qianwen Shao; Xianquan Zhan (EPMA Journal, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Application of malrstone-based conditioner and plantation of Jerusalem artichoke improved properties of saline-alkaline soil in Inner Mongolia - Yujie Zhou; Tianyun Shao; Guotao Men; Jiahao Chen; Na Li; Xiumei Gao; Xiaohua Long; Zed Rengel; Ming Zhu (Journal of Environmental Management, 2023)

Roles of microRNAs and exosomes in Helicobacter pylori associated gastric cancer - Xiao-Han Xu; Shu-Li Shao; Dong Guo; Li-Na Ge; Zan Wang; Peng Liu; Yuan-Yong Tao (Molecular Biology Reports, 2023)

Research progress on function of NAC transcription factors in tomato (Solanum lycopersicum L.) - Na Chen; Qin Shao; Qineng Lu; Xiaopeng Li; Yang Gao; Qiusheng Xiao (Euphytica, 2023)

Proteome landscape and spatial map of mouse primordial germ cells - Pan Wang; Yilong Miao; Xiao-Han Li; Na Zhang; Qilong Wang; Wei Yue; Shao-Chen Sun; Bo Xiong; Jie Qiao; Mo Li (Science China Life Sciences, 2021)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Fn14 Participates in Neuropathic Pain Through NF-κB Pathway in Primary Sensory Neurons - Li-Na Huang; Yun Zou; Shao-Gen Wu; Hong-Hong Zhang; Qing-Xiang Mao; Jin-Bao Li; Yuan-Xiang Tao (Molecular Neurobiology, 2019)

Regulation of osteoblast behaviors via cross-talk between Hippo/YAP and MAPK signaling pathway under fluoride exposure - Wen-qing Zhu; Ying-juan Yu; Li-na Xu; Pan-pan Ming; Shui-yi Shao; Jing Qiu (Journal of Molecular Medicine, 2019)

OsCDC48/48E complex is required for plant survival in rice (Oryza sativa L.) - Lei Shi; Xiao-bo Zhang; Yong-feng Shi; Xia Xu; Yuqing He; Guosheng Shao; Qi-na Huang; Jian-li Wu (Plant Molecular Biology, 2019)

Genomic Selection Using BayesCπ and GBLUP for Resistance Against Edwardsiella tarda in Japanese Flounder (Paralichthys olivaceus) - Yang Liu; Sheng Lu; Feng Liu; Changwei Shao; Qian Zhou; Na Wang; Yangzhen Li; Yingming Yang; Yingping Zhang; Hejun Sun; Weiwei Zheng; Songlin Chen (Marine Biotechnology, 2018)

The Madden–Julian oscillation during the 2016 summer and its possible impact on rainfall in China - Xiaolu Shao; Shuanglin Li; Na Liu; Jie Song (International Journal of Climatology, 2018)
The summer rainfall in China in 2016 exhibited a substantial intraseasonal feature, with an intensification in June and July but a suppression in August over the Yangtze River Basin and North China. The Madden–Julian oscillation (MJO) during the summer and its impact on rainfall in China are investigated by conducting observational analyses and diagnostic linear baroclinic model (LBM) experiments. A significant MJO activity in the summer is observed with three MJO episodes corresponding to three stages of rainfall in China. The LBM is utilized to diagnose the circulation response to the tropical heating forcing associated with each MJO episode. The results suggest that much of the atmospheric circulation linked to the anomalous rainfall is attributed to the strong MJO episodes. During June–July (August), the enhanced (suppressed) convection over the tropical Indian Ocean along with the suppressed (enhanced) convection over the South China Sea (SCS) to the western Pacific excite an ‘East Asian–Pacific’ north‐eastward‐propagating Rossby wave train, inducing anomalous low‐level anticyclonic (cyclonic) flows over the northern SCS and the western North Pacific but cyclonic (anticyclonic) flows over North China. They lead to a westward (eastward) shift and strengthening (weakening) of the western Pacific subtropical high, thus favouring the intensification (suppression) in rainfall over the Yangtze River Basin and North China along with the opposite variation over South China. Relative to the first MJO episode, the MJO convection in the second episode causes a northward movement of the anomalous rainfall band from the Yangtze River Basin to North China. Apart from the impact on the above regions, the first (second and third) MJO episode favours an increase (reduction) in rainfall over Northeast China.

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

Locus Mapping, Molecular Cloning, and Expression Analysis of rps6kb2, a Novel Metamorphosis-Related Gene in Chinese Tongue Sole (Cynoglossus semilaevis) - Yang Liu; Min Wei; Hua Guo; Changwei Shao; Liang Meng; Wenteng Xu; Na Wang; Lei Wang; Deborah M Power; Jilun Hou; Shahid Mahboob; Zhongkai Cui; et al. (Marine Biotechnology, 2017)

Overexpression of PLK3 Mediates the Degradation of Abnormal Prion Proteins Dependent on Chaperone-Mediated Autophagy - Hui Wang; Chan Tian; Jing Sun; Li-Na Chen; Yan Lv; Xiao-Dong Yang; Kang Xiao; Jing Wang; Cao Chen; Qi Shi; Qi-Xiang Shao; Xiao-Ping Dong (Molecular Neurobiology, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

New milbemycin metabolites from the genetically engineered strain Streptomyces bingchenggensis BCJ60 - Jian-Song Li; Min-Na Du; Hui Zhang; Ji Zhang; Shao-Yong Zhang; Hai-Yan Wang; An-Liang Chen; Ji-Dong Wang; Wen-Sheng Xiang (Natural Product Research, 2017)

Identification and functional analysis of the GTPV bidirectional promoter region - Hui Zhang; Zhihua Sun; Na Zhang; Zhiqiang Li; Pengyan Wang; Qiang Fu; Yan Ren; Xuehua Shao; Yu Zhang; Zhiru Guo; Chuangfu Chen (Archives of Microbiology, 2017)

Generation of obese rat model by transcription activator-like effector nucleases targeting the leptin receptor gene - Yuting Chen; Wenqing Lu; Na Gao; Yi Long; Yanjiao Shao; Meizhen Liu; Huaqing Chen; Shixin Ye; Xueyun Ma; Mingyao Liu; Dali Li (Science China Life Sciences, 2017)
The laboratory rat is a valuable mammalian model organism for basic research and drug discovery. Here we demonstrate an efficient methodology by applying transcription activator-like effector nucleases (TALENs) technology to generate Leptin receptor ( Lepr ) knockout rats on the Sprague Dawley (SD) genetic background. Through direct injection of in vitro transcribed mRNA of TALEN pairs into SD rat zygotes, somatic mutations were induced in two of three resulting pups. One of the founders carrying bi-allelic mutation exhibited early onset of obesity and infertility. The other founder carried a chimeric mutation which was efficiently transmitted to the progenies. Through phenotyping of the resulting three lines of rats bearing distinct mutations in the Lepr locus, we found that the strains with a frame-shifted or premature stop codon mutation led to obesity and metabolic disorders. However, no obvious defect was observed in a strain with an in-frame 57 bp deletion in the extracellular domain of Lepr . This suggests the deleted amino acids do not significantly affect Lepr structure and function. This is the first report of generating the Lepr mutant obese rat model in SD strain through a reverse genetic approach. This suggests that TALEN is an efficient and powerful gene editing technology for the generation of disease models.

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

Sirtuin-3 (SIRT3) protects pancreatic β-cells from endoplasmic reticulum (ER) stress-induced apoptosis and dysfunction - Hao-Hao Zhang; Xiao-Jun Ma; Li-Na Wu; Yan-Yan Zhao; Peng-Yu Zhang; Ying-Hui Zhang; Ming-Wei Shao; Fei Liu; Fei Li; Gui-Jun Qin (Molecular and Cellular Biochemistry, 2016)

Arctigenin Confers Neuroprotection Against Mechanical Trauma Injury in Human Neuroblastoma SH-SY5Y Cells by Regulating miRNA-16 and miRNA-199a Expression to Alleviate Inflammation - Jie Song; Na Li; Yang Xia; Zhong Gao; Sa-Feng Zou; Yu-Hui Yan; Shao-Heng Li; Yue Wang; Ya-Kun Meng; Jing-Xian Yang; Ting-Guo Kang (Journal of Molecular Neuroscience, 2016)

Identification of antigenic domains in the non-structural protein of Muscovy duck parvovirus - Tian-fei Yu; Ming Li; Bing Yan; Shu-li Shao; Xing-dong Fan; Jia Wang; Dan-na Wang (Archives of Virology, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

Potential probiotic attributes of a new strain of Bacillus coagulans CGMCC 9951 isolated from healthy piglet feces - Shao-Bin Gu; Li-Na Zhao; Ying Wu; Shi-Chang Li; Jian-Rui Sun; Jing-Fang Huang; Dan-Dan Li (World Journal of Microbiology and Biotechnology, 2015)

Rapid evaluation of reference evapotranspiration in Northern China - Shao-hua Zhao; Yong-hui Yang; Feng Zhang; Xin-xin Sui; Yun-jun Yao; Na Zhao; Qiuxiao Zhao; Chun-qiang Li (Arabian Journal of Geosciences, 2015)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Numerical modeling of PP- and PS-wave azimuthal anisotropy in HTI media - Zhong-Ping Qian; Shao-Hua Zhang; Bo Zhao; Na Lei; Xiang-Yang Li (Applied Geophysics, 2012)

Purification, Characterization, and Expression Analysis of a Putative Lectin in Peanut (Arachis hypogaea L.) - Sun Jie; Zhang Chu-shu; Yu Li-na; Bi Jie; Liu Shao-fang; Zhu Feng; Yang Qing-li (Plant Molecular Biology Reporter, 2012)

The mechanism of mimecan transcription induced by glucocorticoid in pituitary corticotroph cells - Xiao Na Zhang; Li Qiong Xue; He Jiang; Shao Ying Yang; Huai Dong Song; Qin Yun Ma (Molecular and Cellular Biochemistry, 2012)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)